2023
DOI: 10.3389/fsufs.2022.1001509
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting fruit and vegetable determinants: Evidence from Latin America

Abstract: IntroductionIn the past decade, the public health discussion regarding fruit and vegetable (FV) consumption has been dominated by economic and physical accessibility.MethodsUsing an online survey in four Latin American countries, we applied a set of tobit models to compare the determinants of desirable and current consumption of FV levels for satisfied and unsatisfied respondents.ResultsWe found that, even when consuming less than five FV portions a day, most of the respondents were satisfied with their curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Silva et al found that 18.7% confirmed that price is the main determinant of the consumption of F&V, furthermore, the authors mentioned that satiety is a key determinant for low socioeconomic status households, unlike middle-status households, where comfort is a determinant when it comes to healthy eating 19 . Educational level and being male are closely related to a poor intake of F&V and healthy food in general 14 .…”
Section: Discussionmentioning
confidence: 95%
“…Silva et al found that 18.7% confirmed that price is the main determinant of the consumption of F&V, furthermore, the authors mentioned that satiety is a key determinant for low socioeconomic status households, unlike middle-status households, where comfort is a determinant when it comes to healthy eating 19 . Educational level and being male are closely related to a poor intake of F&V and healthy food in general 14 .…”
Section: Discussionmentioning
confidence: 95%